New York Paper - The North Staffordshire Coal and Iron District - William Hamilton Merritt (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1880)
In this paper, which I have the honor to submit to the Institute, it is my intention to treat especially of that part of the North Staffordshire field which converges to a long tongue in the neighborhood of Congleton, and which includes the villages of New Chapel, Ford Green, Norton, Biddulph, Bradley Green, Gillow Heath, and the immediate vicinity. My object-is not so much to give a minute description of the geology or systems of mining and smelting, as by a general review, some idea of the extraordinary facilities for the production of excellent iron, which have enabled this district to maintain its position more successfully than any of its rivals against the late depression in trade. The North Staffordshire coal field has the Cheshire and Laucashire fields some thirty-five miles to the north, those of Derbyshire and Nottinghamshire forty miles to the east, those of South Staffordshire and Shropshire, about thirty miles to the south, and the Denbighshire and Flintshire fields some forty miles to the west. It is highly probable that the coal continues under the new red sandstone to the Western and Southern fields as the dips on both sides, and absence of large faults, make it impossible to come to any other conclusion. In a section of this coal field, from Chatterly to Whitfield, thirtytwo workable seams of coal are shown, of an aggregate thickness of 130 feet, varying from 2 feet 6 inches to 7 feet, and thirteen seams of ironstone, 24 feet, averaging from 2 to 4 feet. All of these seams have been minutely described in a paper by Mr. Charles J. Homer, read in 1875 before the British Iron and Steel Institute. In the northern part, to which I especially wish to direct your attention, the beds lie in a V-shaped basin, the underlying millstone grit and Yoredale rocks rising and forming escarpments on either side of the valley containing the coal. Throughout this district, at the outcrop of the coal, there are indications of old workings. A shaft 4 to 5 feet in diameter reaches the coal at about 14 yards from the surface, and from it the coal has